The Lost Child - Scott, Rolf Erik; Smedal, Olaf (Journal of Anthropological Films, 2025)
This film chronicles a two-day rite of passage known as Nuka Nua, or ‘Returning to one's home village’ among the Ngadha people in central Flores, Indonesia. Nine years earlier, Ludis, a noblewoman and nurse, secretly married her beloved, Anis, a schoolteacher and commoner. In their society, women preserve the noble lineage, which is severed through hypogamy (marrying beneath one's status), once punishable by death. The couple have two children and Ludis has been exiled from her village since their marriage. Ludis's aging parents, Bene and Sofie, have been longing to spend time with their only adopted child and grandchildren. However, a family reunion can only occur after Ludis and Anis have passed through a harrowing rite of passage that cleanses them and transforms Ludis from a noble woman to a commoner. This ritual of death and rebirth is prohibitively expensive, forcing the eloped couple to endure a long wait before it could be arranged. The film shows how two fundamentally different ideological constructs clash. One manifests as a social organization characterized by hereditary rank based on notions of purity; the other echoes more egalitarian notions. The first is rooted in the cosmo-mythical past; the second is grounded in a much more recent discourse. Social organization premised on rank and purity is rapidly losing ground– in part due to the influence of ‘the modern’, but even more so because its own internal logic works against it. Warning: This film has scenes showing the sacrifice and slaughter of animals.